2011
DOI: 10.2308/aud.2011.30.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Growth in the Public Accounting Industry: The Roles of Information Technology and Human Capital

Abstract: SUMMARY: In this paper we decompose productivity growth into four components: efficiency change, technical progress, information technology (IT) capital accumulation, and human capital accumulation. We analyze data on the operations of 51 public accounting firms in Taiwan for the years 1993 and 2003, and find that productivity growth was driven primarily by the accumulation of IT capital and human capital. We also find that the difference in productivity growth between Big 4 and non-Big 4 accounting firms is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 42 publications
0
23
0
1
Order By: Relevance
“…Norwegian data from Sapprasert (2007) show that the productivity benefits from IT adoption in service industries increase with the size of the firm. Chang, Chen, Duh, and Li (2011) find that larger auditing firms have larger productivity returns on IT use. This paper will explore the hypothesis that jobs mismatch may be one of the causes of the low contribution of IT to small service firms' efficiency, since small service firms may not completely optimize human resource practices (Altinay, Altinay, & Gannon, 2008;Chaston, 1998;Jameson, 2000).…”
Section: Introductionmentioning
confidence: 95%
“…Norwegian data from Sapprasert (2007) show that the productivity benefits from IT adoption in service industries increase with the size of the firm. Chang, Chen, Duh, and Li (2011) find that larger auditing firms have larger productivity returns on IT use. This paper will explore the hypothesis that jobs mismatch may be one of the causes of the low contribution of IT to small service firms' efficiency, since small service firms may not completely optimize human resource practices (Altinay, Altinay, & Gannon, 2008;Chaston, 1998;Jameson, 2000).…”
Section: Introductionmentioning
confidence: 95%
“…Both education and work experience foster the development of expertise in auditing (Bonner & Pennington, ; Hitt, Bierman, Schimizu, & Kochhar, ). Prior empirical findings demonstrate positive consequences of education and general experience for the profitability of audit firms (e.g., Bröcheler, Maijoor, & van Witteloostuijn, ; Chang, Chen, Duh, & Li, ) and demonstrate an association between task‐specific expertise of auditors and task performance (e.g., Bedard, ; Bedard & Biggs, ; Bonner & Lewis, ; Hammersley, ). In this respect, task‐specific training initiatives are associated with improved performance for tasks such as analytical procedures (Moreno, Bhattacharje, & Brandon, ) and a ratio analysis (Bonner & Walker, ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Apart from the previous issues, Chang et al. () and Banker et al. () indicated that competitive long‐term performance is sustained by core resources, such as physical, human, organizational, and financial capitals.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have incorporated various DEA models to measure the efficiency and improve the productivity of this complicated system in the accounting industry (e.g., Boyd, ; Flesher et al., ; Gammie and Joyce, ). These studies have mostly assessed the efficiency of business firms using the black box concept to measure performance (Chang et al., , , ). These studies have most often used traditional DEA with relatively simple structures (Banker et al., , 2005; Cheng, ), that is, structures that include only one activity (assuming that such an activity is regarded as a black box).…”
Section: Introductionmentioning
confidence: 99%